Valorisation of spent cultivated meat media for recombinant FGF2 production in Lactococcus lactis - Juliana Rizal; Prashant Mainali; Jun Ping Quek; Lee Ling Tan; Jiawu Bi; Alson Jianchen Chan; Azra Anwar Gaffoor; Lamony Jian Ming Chew; Shigeki Sugii; Say Kong Ng; Dave Siak-Wei Ow; Fong Tian Wong (Systems Microbiology and Biomanufacturing, 2025)

Identification of the Shuanglongtan tectonic mélange (ca. 1.7–1.5 Ga) in the southwestern Yangtze Block and it’s tectonic implications - Jun-Ping Liu; Zai-Bo Sun; Xiao-Hu He; Jiang-Tai Zhao; Shi-Jun He; Ling-Jing Bi; Wei-Ke Li (Precambrian Research, 2025)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Relevance and mechanism of STAT3/miR-221-3p/Fascin-1 axis in EGFR TKI resistance of triple-negative breast cancer - Lu-Lu Jin; Hua-Jun Lu; Jun-Kang Shao; Yan Wang; Shi-Ping Lu; Bi-Fei Huang; Gui-Nv Hu; Hong-Chuan Jin; Chao-Qun Wang (Molecular and Cellular Biochemistry, 2024)

The impacts of spatio-temporal variation of natural and agricultural influences on the environmental water quality in a fluvial-lacustrine watershed in China - Yu Feng; Bing-Hui Zheng; Hai-Feng Jia; Bing-Bing Song; Yang Liu; Jun-Ping Bi (Environmental Science and Pollution Research, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Loss of Myomixer Results in Defective Myoblast Fusion, Impaired Muscle Growth, and Severe Myopathy in Zebrafish - Ping Wu; Pengzheng Yong; Zhanxiong Zhang; Rui Xu; Renjie Shang; Jun Shi; Jianshe Zhang; Pengpeng Bi; Elizabeth Chen; Shaojun Du (Marine Biotechnology, 2022)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Transcriptome analysis reveals genes associated with leaf color mutants in Cymbidium longibracteatum - Jiang Yu; Wang Qiang; Shen Qin-Qin; Zhuo Bi-Ping; He Jun-Rong (Tree Genetics & Genomes, 2020)

Aquatic bioaccumulation and trophic transfer of tetrabromobisphenol-A flame retardant introduced from a typical e-waste recycling site - Lin Tao; Jiang-Ping Wu; Hui Zhi; Ying Zhang; Zi-He Ren; Xiao-Jun Luo; Bi-Xian Mai (Environmental Science and Pollution Research, 2016)

Species-Specific Bioaccumulation of Halogenated Organic Pollutants and Their Metabolites in Fish Serum from an E-Waste Site, South China - Yan-Hong Zeng; Xiao-Jun Luo; Xiao-Bo Zheng; Bin Tang; Jiang-Ping Wu; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2014)

Sex identification and genetic variation of Saccharina (Phaeophyta) gametophytes as revealed by inter-simple sequence repeat (ISSR) markers - Jun-Gang Gu; Yu-Ping Sun; Yu Liu; Yan-Hui Bi; Zhi-Gang Zhou (Journal of Applied Phycology, 2014)

Purification of contaminated paddy fields by clean water irrigation over two decades - Yiping Tai; Huanping Lu; Zhian Li; Ping Zhuang; Bi Zou; Hanping Xia; Faming Wang; Gang Wang; Jun Duan; Jianxia Zhang (Environmental Geochemistry and Health, 2013)

Dynamic distribution and tissue tropism of infectious laryngotracheitis virus in experimentally infected chickens - Lin-Guo Wang; Jun Ma; Chun-Yi Xue; Wei Wang; Chao Guo; Feng Chen; Jian-Ping Qin; Ning-Hai Huang; Ying-Zuo Bi; Yong-Chang Cao (Archives of Virology, 2013)

Phylogenetic analysis of hemagglutinin genes of 40 H9N2 subtype avian influenza viruses isolated from poultry in China from 2010 to 2011 - Feng Chen; Zhuan-Qiang Yan; Jun Liu; Jun Ji; Shuang Chang; Di Liu; Jian-Ping Qin; Jing-Yun Ma; Ying-Zuo Bi; Qing-Mei Xie (Virus Genes, 2012)

Analysis of indica- and japonica-specific markers of Oryza sativa and their applications - Xiao-Jun Dai; Yuan-Zhu Yang; Liang Zhou; Li-Jun Ou; Man-Zhong Liang; Wen-Jia Li; Gong-Ping Kang; Liang-Bi Chen (Plant Systematics and Evolution, 2012)

Permissible Value for Vanadium in Allitic Udic Ferrisols Based on Physiological Responses of Green Chinese Cabbage and Soil Microbes - Xi-yuan Xiao; Miao Yang; Zhao-hui Guo; Yue-ping Luo; Jun-ping Bi (Biological Trace Element Research, 2012)

Curcumin promotes cholesterol efflux from adipocytes related to PPARgamma–LXRalpha–ABCA1 passway - Shao-zhuang Dong; Shui-ping Zhao; Zhi-hong Wu; Jun Yang; Xiang-zhu Xie; Bi-lian Yu; Sai Nie (Molecular and Cellular Biochemistry, 2011)

Tissue-specific and expression of porcine growth hormone gene in BAC transgenic mice - Jia Tong; Simon G. Lillico; Ming Jun Bi; Tong Qing; Xiao Fang Liu; YuanYuan Wang; Min Zheng; Meili Wang; Yun Ping Dai; C. Bruce A. Whitelaw; Ning Li (Transgenic Research, 2011)

Isolation and expression analysis of LEA genes in peanut (Arachis hypogaea L.) - Lei Su; Chuan-Zhi Zhao; Yu-Ping Bi; Shu-Bo Wan; Han Xia; Xing-Jun Wang (Journal of Biosciences, 2011)

Characterization of Five Putative Acyl Carrier Protein (ACP) Isoforms from Developing Seeds of Arachis hypogaea L. - Meng-Jun Li; Xing-Jun Wang; Lei Su; Yu-Ping Bi; Shu-Bo Wan (Plant Molecular Biology Reporter, 2010)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

Molecular mechanism underlying differential apoptosis between human melanoma cell lines UACC903 and UACC903(+6) revealed by mitochondria-focused cDNA microarrays - Qiuyang Zhang; Jun Wu; AnhThu Nguyen; Bi-Dar Wang; Ping He; Georges St. Laurent; Owen M. Rennert; Yan A. Su (Apoptosis, 2008)

Partial characterization of a hydrophobin protein Po.HYD1 purified from the oyster mushroom Pleurotus ostreatus - Ai Min Ma; Lin Jun Shan; Hui Jie Wang; Zhao Ping Du; Bi Jun Xie (World Journal of Microbiology and Biotechnology, 2008)